Q: 6r plus 5s-5r equals

Write your answer...

Submit

Related questions

What is ; -r-8+6r=-13.=]

r=8

6r+2=2 subtract 2 on each side. 6r=0 divide each side by 6 r=zero

-6r-5 = 7-12r 12r-6r = 7+5 6r = 12 r = 2

The 'solution' is the number that 'r' must be in order to make the statement true.Here's how to find it:6r - 1 + 6r = 11Add 1 to each side:6r + 6r = 12Clean up the left side:12r = 12Divide each side by 12:r = 1

3+10-r+6r = -3+9r+0 13+5r = -3+9r 16 = 4r r = 4

3.333

5 - 710 - 6r = -93-705 - 6r = -93 705 + 6r = 93 6r = 93 - 705 = -612 r = -612/6 = -102

Commutatitivity of addition in the fact that you can change the order of 11s and 3t. But also associativity of addition in that you can write the sum of three terms without the need for brackets to show which addition needs to be performed first.

If that's the equation 6r + 7 = 13 + 7r, r = -6

21 4t2+6r-tr 4[-3]2+6[5]-[-3][5] 8[-3]+30-[-15] -24+30+15=21

12 - 6r = 2r + 36Add 6r to each side:12 = 8r + 36Subtract 36 from each side:-24 = 8rDivide each side by 8:r = -3

-6r + 1 = -17, then (17+1)=18=6r, so r=(18/6)=3. The answer is r=3

3q+4r-s+5q-6r+2s

If: 5/6r = 2/3 then r = 5/4 or 1.25

-2r

5r + r = 6r

r2+6r-7 = (r+7)(r-1) when factored

3r + 3r + 2t = 6r + 2t

90

Type your answer here... 6R-12 = 2R + 36 subtract 2R from both sides 4R -12 = 36 add 12 to both sides 4R = 48 divide both sides by 4 R = 12

9r = 3r + 6 subtract 3r from both sides 6r = 6 divide both sides by 6 r=1 ■

(6r - 7v)(3r - 2v)

-6r - s

When the following expression is written in simplest form what is the coefficient of the variable term -1.5r plus 6r and ndash 12.2r?